Exosomes in Cancer: Circulating Immune-Related Biomarkers. (11th December 2019) - Głuszko, Alicja; Szczepański, Mirosław J.; Ludwig, Nils; Mirza, Shafaq M.; Olejarz, Wioletta
Abstract : Exosomes, the smallest vesicles (30–100 nm) among multivesicular bodies, are released by all body cells including tumor cells. The cargo they transfer plays an important role in intercellular communication. Tumor-derived exosomes (TEXs) maintain interactions between cancer cells and the microenvironment. Emerging evidence suggests that tumor cells release a large number of exosomes, which may not only influence proximal tumor cells and stromal cells in the local microenvironment but can also exert systemic effects as they are circulating in the blood. TEXs have been shown to boost tumor growth promote progression and metastatic spread via suppression or modification of the immune response towards cancer cells, regulation of tumor neo-angiogenesis, pre-metastatic niche formation, and therapy resistance. In addition, recent studies in patients with cancer suggest that TEXs could serve as tumor biomarker reflecting partially the genetic and molecular content of the parent cancer cell (i.e., as a so-called "liquid biopsy"). Furthermore, recent studies have demonstrated that exosomes may have immunotherapeutic applications, or can act as a drug delivery system for targeted therapies with drugs and biomolecules.